PECULIARITIES OF THE INTRODUCTION OF MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE COURTS (Conference Zone, 2021)
This article discusses the challenges of digitizing courts and achieving justice in the Republic of Uzbekistan, the experience of the United States and Germany in this area, and the digitization of the judiciary